Mobile technology identity and self-efficacy: Implications for the adoption of clinically supported mobile health apps. (December 2019) - Balapour, Ali; Reychav, Iris; Sabherwal, Rajiv; Azuri, Joseph
Highlights: Mobile technology identity affects patients' intention to adopt mHealth apps. Self-efficacy affects patients' intention to adopt mHealth apps. Prior experience affects patients' intention to adopt mHealth apps. Education negatively affects patients' intention to adopt mHealth apps. Prior experience affects Mobile technology identity and self-efficacy. Abstract: Despite smartphone applications (apps) being key enablers of telemedicine, telehealth, and self-monitoring, adoption issues persist for mobile healthcare (mHealth) apps. This study diverged from the traditional adoption approach and drew on more innovative theories to predict the intentions of patients for adopting apps supported by clinics. More specifically, technology identity literature was explored to make this prediction and the study surveyed 292 patients who were seated in the waiting room of a local clinic. The results suggested that perceived mobile technology identity (MTI), perceived related IT experience, and perceived self-efficacy positively influences patients' perceived intentions to adopt mHealth apps provided by clinics or hospitals. Furthermore, the results suggested that perceived related IT experience positively influences users perceived self-efficacy and perceived MTI. However, education was found to negatively influence patients' perceived intentions to use mHealth apps. This study contributes to the growing literature on the use of these apps in trying to elevate the quality of patients' lives. Moreover, there are implications for mHealth-app designers who are trying to make healthcare services accessible via smartphones.